2021
DOI: 10.1177/23743735211065274
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Use of In-Person and Telehealth Primary Care Among High- and Low-Risk Medicare Beneficiaries During COVID-19

Abstract: We conducted a retrospective cohort study using a difference-in-differences design to estimate differences in primary care outpatient clinic visit utilization among high- and low-risk Medicare aging beneficiaries from an Accountable Care Organization during the COVID-19 pandemic compared to a control cohort from the previous year. High-risk was defined as having a Hierarchical Condition Category score of 2 or higher. A total of 582 101 patient-month records were analyzed. After adjusting for patient characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
(66 reference statements)
1
15
0
Order By: Relevance
“…Older patients may be more likely to face added challenges when adopting new technologies; however, they may benefit more than younger patients from using telehealth services due to challenges of transportation and costs associated with in-person visits. 44 During the COVID-19 pandemic digital access gaps among older adults may have grown in view of economic hardship and social isolation. 45 , 46 Our findings suggest that additional interventions targeting care coordination and engagement of older Medicare beneficiaries are needed to avoid increasing disparities in healthcare access.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients may be more likely to face added challenges when adopting new technologies; however, they may benefit more than younger patients from using telehealth services due to challenges of transportation and costs associated with in-person visits. 44 During the COVID-19 pandemic digital access gaps among older adults may have grown in view of economic hardship and social isolation. 45 , 46 Our findings suggest that additional interventions targeting care coordination and engagement of older Medicare beneficiaries are needed to avoid increasing disparities in healthcare access.…”
Section: Discussionmentioning
confidence: 99%
“… 17 International evidence confirms that older patients, those with visual, hearing, or cognitive impairment, those from ethnic minority and rural backgrounds, and the socially deprived are less likely to be reached by telehealth services, risking increasing health disparities. 18 21 However, in NZ a study showed that telehealth actually reduced access barriers for indigenous Māori. 22…”
Section: Discussionmentioning
confidence: 99%
“…17 International evidence confirms that older patients, those with visual, hearing or cognitive impairment, those from ethnic minority and rural backgrounds and the socially deprived are less likely to be reached by telehealth services, risking increasing health disparities. [18][19][20][21] However, in New Zealand a study showed that telehealth actually reduced access barriers for Indigenous 22 Although Starfield's definition of primary care related to system level attributes, there was evidence that the pandemic-induced changes in the general practice model reflected attempts to maintain some of these attributes at a practice level. Practices coordinated health care despite lack of support from other services.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…On average, the ACO served about 21 000 to 22 000 Medicare fee-for-service beneficiaries each year, among whom 90.3% were 65 years or older. 10 , 31 …”
Section: Methodsmentioning
confidence: 99%